2023
DOI: 10.1002/alz.12955
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 is associated with earlier symptom onset in LOAD but later symptom onset in EOAD

Abstract: Background:We studied the effect of apolipoprotein E (APOE) ε4 status and sex on age of symptom onset (AO) in early-(EO) and late-(LO) onset Alzheimer's disease (AD).Method: A total of 998 EOAD and 2562 LOAD participants from the National Alzheimer's Coordinating Center (NACC) were included. We used analysis of variance to examine AO differences between sexes and APOE genotypes and the effect of APOE ε4, sex, and their interaction on AO in EOAD and LOAD, separately.Results: APOE ε4 carriers in LOAD had younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Below age 60, however, early‐onset AD patients are equally likely to be APOE ε3/ε3 homozygotes 26,28 . Elsewhere, a recent study observed no effect of APOE ε4 on age of onset in men with early‐onset AD, but a decreased age of onset for females with early‐onset AD lacking an APOE ε4 allele 29 . That APOE ε4 plays less of a role in the earliest onset cases of AD further argues against the hypothesis that early‐onset AD is merely explained by an enrichment of late‐onset AD common genetic risk variants.…”
Section: Discussionmentioning
confidence: 99%
“…Below age 60, however, early‐onset AD patients are equally likely to be APOE ε3/ε3 homozygotes 26,28 . Elsewhere, a recent study observed no effect of APOE ε4 on age of onset in men with early‐onset AD, but a decreased age of onset for females with early‐onset AD lacking an APOE ε4 allele 29 . That APOE ε4 plays less of a role in the earliest onset cases of AD further argues against the hypothesis that early‐onset AD is merely explained by an enrichment of late‐onset AD common genetic risk variants.…”
Section: Discussionmentioning
confidence: 99%
“…Tau‐mediated neurodegeneration may also be markedly exacerbated by APOE ε4 , leading to increased tau deposition 20,21 . APOE ε4 is associated with earlier symptom onset in LOAD and possibly a later symptom onset in EOAD, though it appears the ε4 allele has maximum impact between the onset ages of 60 to 70 years 4,22,23 . Further, Polsinelli et al 4 .…”
Section: Introductionmentioning
confidence: 96%
“…20,21 APOE ε4 is associated with earlier symptom onset in LOAD and possibly a later symptom onset in EOAD, though it appears the ε4 allele has maximum impact between the onset ages of 60 to 70 years. 4,22,23 Further, Polsinelli et al 4 found female EOAD APOE ε4 non-carriers had significantly younger symptom onset compared to female ε4 carriers and males regardless of their APOE ε4 status, suggesting a complex age-and sex-dependent relationship between APOE ε4 and AD. 24 EOnonAD patients are less likely to be APOE ε4 carriers, with a low, 14%, prevalence of the gene.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple Mendelian randomization studies have indicated a causal relationship between Alzheimer's disease (AD) and COVID-19 [22,23] . Some of the same mutated genes have also been found to co-exist in both diseases, such as double mutations in the apolipoprotein E (APOE4) allele [24][25][26] . Additionally, the binding of SARS-CoV-2 viral proteins to host mitochondrial proteins may inhibit oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%